The Buddha in the attic [large type] - Otsuka, Julie, 1962- (Thorndike Press large print basic series., 2012)
Presents the stories of six Japanese mail-order brides whose new lives in early twentieth-century San Francisco are marked by backbreaking migrant work, cultural struggles, children who reject their heritage, and the prospect of wartime internment.